A whirligig-inspired intermittent-contact triboelectric nanogenerator for efficient low-frequency vibration energy harvesting. (December 2021) - Fan, Kangqi; Wei, Danmei; Zhang, Yan; Wang, Peihong; Tao, Kai; Yang, Rusen
Abstract: Triboelectric nanogenerator (TENG) has overwhelming dominance in the exploitation of low-frequency vibration energy, but the sparse pulsed output, material abrasion in contact-mode TENG and output decline in noncontact-mode TENG limit the output power and electrical stability. Herein, we report a rotational intermittent-contact TENG (IC-TENG) that is realized on the basis of a slideable rope-driven rotor to achieve efficient exploitation of low-frequency vibrations. The rope-driven rotor can start to spin and transform low-frequency vibrations to high-speed rotation through a whirligig-like dynamics mechanism without the requirement of any hand operation, which enables frequency-multiplied and high electric output of the IC-TENG. Moreover, owing to the constantly replenished tribo-charges produced by the intermittent sliding contact between the rotator and stator in the rope-driven rotor, the IC-TENG exhibits high electrical stability, whose normalized electric output stabilizes at around 81%, whereas the normalized electric output of noncontact-mode TENG attenuates continuously to 48% over a 10-day span. The frequency-multiplied electric output and superior electrical stability make the IC-TENG a promising technology for harnessing ambient low-frequency vibration energy. This work demonstrates a novel strategy for TENG to achieve high electric output and in the meanwhile long-term stability. Graphical abstract: ga1 Highlights: The IC-TENG realizes vibration-to-rotation conversion through whirligig-like dynamics. The IC-TENG can effectively harvest low-frequency vibrations without any manual operation. The IC-TENG can switch between contact mode and noncontact mode automatically. The IC-TENG exhibits excellent electrical stability and mechanical durability. The device represents a green power source for both wearable and low-power electronics.